COMPOSITE COMPLEX UNITS OF RUSSIAN WORD FORMATION : GENERAL CHARACTERISTICS OF COMPOSITIONAL WORD-FORMATION NESTS - Shoira Rikhsibaevna, Ramazanova (ANTIS PUBLISHER, 2024)
General Background: Compound words are an integral part of A.N. Tikhonov’s Word Formation Dictionary of the Russian Language, reflecting the dynamic nature of the Russian lexicon. Specific Background: Tikhonov’s systematic approach categorizes compound words within a word-formation paradigm, showcasing their role at various stages of derivation. Knowledge Gap: Despite their significance, there is limited analysis on how compound words, especially from the быстрый (fast) family, influence the broader Russian word-formation system. Aims: This study aims to analyze the compound word family of быстрый and explore its role within Tikhonov's framework, demonstrating how compound words contribute to the linguistic flexibility and precision of the Russian language. Results: The analysis reveals that compound words derived from быстрый display a diverse array of meanings and grammatical forms, showcasing the productive nature of compound word formation across different parts of speech. Novelty: This study highlights the interconnectedness of word-formation families, with compound words serving as a bridge between different grammatical categories, thus contributing to the adaptability of the language. Implications: The findings underscore the importance of compound words in understanding the morphological evolution of Russian, offering insights into how lexemes evolve and adapt to meet communicative needs.